Air Quality Monitoring System Using IoT - Razak, Nurul Syahidah; Homam, Mariyam Jamilah (Evolution in Electrical and Electronic Engineering, 2024)
Air pollution originating from vehicles and industries has become a serious problem posing a threat to human life. Therefore, air quality monitoring is crucial for both outdoor and indoor applications to safeguard a promising future and ensure a healthier life. This project developed an air quality monitoring system that allows users to monitor and examine air quality directly at a specific location using the Internet of Things (IoT). The system employs two types of sensors: fine dust sensor (GP2Y1010AU0F) and temperature with humidity sensor (DHT11) which transmit data to NodeMCU ESP32. This microcontroller processes and sends the data to the Blynk web server. The project also incorporates Long Range (LoRa) module as the transmitter and receiver for the sensor data. Results are compared with TESTO 650i. There were some inconsistencies with readings which could be due to sensors’ accuracy or environmental factors. The integration of this system with cloud storage enhances the efficiency of information delivery. An IoT-based system like this is essential for users who wish to conduct real-time remote monitoring. Ultimately, this project serves as a method to detect fine dust and monitor air quality readings including temperature and humidity.